Isothermal crystallization study and mechanical properties of polypropylene/polystyrene/styrene-ethylenebutadiene- styrene blends - Selamat, Nur Zalina (2015)
An understanding of the crystallization process kinetics is important for the selection of processing parameters and product properties control. In this study, the isothermal crystallization of polypropylene/polystyrene/styrene-ethylene-butadienestyrene (PP/PS/SEBS) blends were evaluated using differential scanning calorimetry (DSC). The blends were prepared by using Brabendar twin screw extruder and samples were then injection molded. 10-15 mg samples were quenched from the melt stage to a range of crystallization temperatures (Tc) between 134-138 C. That samples were held at these selected temperatures until the calorimeter response returned to the baseline. Isothermal crystallization data were then analyzed using Avrami kinetics model and Hoffman-Weeks theory. The increase of amorphous PS and SEBS content in system blends led to the decreases in the crystallization rate. The region covered for Avrami exponent, n, was between 1.97 to 3.2 (±0.1), indicating that heterogeneous nucleation of spherulites occurred and the growth of spherulites was between two-dimensional and three-dimensional for primary crystallization process of the blends. Equilibrium melting temperature (Tm°) obtained through Hoffman-Weeks theory was found to decrease with increasing PS and SEBS contents. The presence of amorphous polymer could disrupt the packing of the crystalline component in the blend, resulting in defective, lower melting point crystallites. The mechanical properties determined from tensile, flexural and impact test revealed that loading of SEBS gave a synergistic effect on flexural properties, and higher loading of SEBS produced superior impact properties. The best stiffness– toughness balance was obtained from the blend of PP/PS 90/10 at 5 phr SEBS loading which also gave fastest crystallization. Morphology studies by scanning electron microscope (SEM) showed finer dispersion of PS with the presence of SEBS into PP/PS blends. SEBS confirmed the improvement of blend compatibility